High Throughput Scheduling Algorithms for Input Queued Packet Switches - Chithra Devi, R.; Jemi Florinabel, D.; Prasanth, Narayanan (Computers, materials & continua, 2022)
The high-performance computing paradigm needs high-speed switching fabrics to meet the heavy traffic generated by their applications. These switching fabrics are efficiently driven by the deployed scheduling algorithms. In this paper, we proposed two scheduling algorithms for input queued switches whose operations are based on ranking procedures. At first, we proposed a Simple 2-Bit (S2B) scheme which uses binary ranking procedure and queue size for scheduling the packets. Here, the Virtual Output Queue (VOQ) set with maximum number of empty queues receives higher rank than other VOQ’s. Through simulation, we showed S2B has better throughput performance than Highest Ranking First (HRF) arbitration under uniform, and non-uniform traffic patterns. To further improve the throughput-delay performance, an Enhanced 2-Bit (E2B) approach is proposed. This approach adopts an integer representation for rank, which is the number of empty queues in a VOQ set. The simulation result shows E2B outperforms S2B and HRF scheduling algorithms with maximum throughput-delay performance. Furthermore, the algorithms are simulated under hotspot traffic and E2B proves to be more efficient.